A. Using the rule \(\displaystyle{\left({x},{y}\right)}\to{\left({x}-{4},{y}+{3}\right)}\)

\(\displaystyle{\left({0},{0}\right)}\to{\left({0}-{4},{0}+{3}\right)}={\left(-{4},{3}\right)}\)

\(\displaystyle{\left({0},{4}\right)}\to{\left({0}−{4},{4}+{3}\right)}={\left(-{4},{7}\right)}\)

\(\displaystyle{\left({2},{0}\right)}\to{\left({2}−{4},{0}+{3}\right)}={\left(-{2},{3}\right)}\)

B. \(\displaystyle{\left({x},{y}\right)}\to{\left(-{x},{y}\right)}\)

\(\displaystyle{\left({0},{0}\right)}\to{\left({0},{0}\right)}\)

\(\displaystyle{\left({0},{4}\right)}\to{\left({0},{4}\right)}\)

\(\displaystyle{\left({2},{0}\right)}\to{\left(-{2},{0}\right)}\)

C. \(\displaystyle{\left({x},{y}\right)}\to{\left(-{y},{x}\right)}\)

\(\displaystyle{\left({0},{0}\right)}\to{\left({0},{0}\right)}\)

\(\displaystyle{\left({0},{4}\right)}\to{\left(-{4},{0}\right)}\)

\(\displaystyle{\left({2},{0}\right)}\to{\left({0},{2}\right)}\)

\(\displaystyle{\left({0},{0}\right)}\to{\left({0}-{4},{0}+{3}\right)}={\left(-{4},{3}\right)}\)

\(\displaystyle{\left({0},{4}\right)}\to{\left({0}−{4},{4}+{3}\right)}={\left(-{4},{7}\right)}\)

\(\displaystyle{\left({2},{0}\right)}\to{\left({2}−{4},{0}+{3}\right)}={\left(-{2},{3}\right)}\)

B. \(\displaystyle{\left({x},{y}\right)}\to{\left(-{x},{y}\right)}\)

\(\displaystyle{\left({0},{0}\right)}\to{\left({0},{0}\right)}\)

\(\displaystyle{\left({0},{4}\right)}\to{\left({0},{4}\right)}\)

\(\displaystyle{\left({2},{0}\right)}\to{\left(-{2},{0}\right)}\)

C. \(\displaystyle{\left({x},{y}\right)}\to{\left(-{y},{x}\right)}\)

\(\displaystyle{\left({0},{0}\right)}\to{\left({0},{0}\right)}\)

\(\displaystyle{\left({0},{4}\right)}\to{\left(-{4},{0}\right)}\)

\(\displaystyle{\left({2},{0}\right)}\to{\left({0},{2}\right)}\)